The Use of the Computer Tomography Method in the Analysis of the Microstructure of Materials Formed as a Result of Hydrothermal Treatment: Cellular Concretes - Stepien, Anna; Dachowski, Ryszard (Journal of composites science, 2024)
The subject of this research is sustainable construction and energy saving, which is most reflected in the technological aspects of building construction. This article focuses on single-family buildings, and the subject of this research is hollow blocks (blocks) created as a result of hydrothermal treatment, in this case, autoclaved aerated concrete (AAC) and autoclaved cellular concrete (ACC), both traditional and modified plastics (HIPS). There are two types of materials resulting from hydrothermal treatment: autoclaved sand-lime bricks and autoclaved concrete. Both in the case of ACC and silicates bricks, the basic substrates used during their production are lime, sand and water (cement is also added to cellular concrete). This article presents the methodology of testing the porous structure of autoclaved materials with the use of computed tomography. Aerated concrete (light autoclaved concrete) has a compressive strength of 2–6 MPa. The tests included aerated concrete modified with high-impact polystyrene, commonly known as HIPS. HIPS high-impact polystyrene is a thermoplastic polymer that is obtained by block suspension polymerization of styrene with the addition of synthetic rubber. As a result of polymerization, small particles of polybutadiene remain in the polystyrene male, changing its physical and mechanical properties. The results from the content of air voids in the autoclaved concrete sample were, on average, 52.53%.